Essential oil composition and antioxidant activity of Levisticum officinale Koch. at various phenological stages - Neda Mohamadi; Peyman Rajaei; Mehran Moradalizadeh; Mohammad Sadegh Amiri (Institue of Medicinal Plants, ACECR, 2017)
Background: The leaves, roots and seeds of Lovage (Levisticum officinale Koch) being used as an herb, vegetable and spice. Objective: The aim of this study is evaluation of the changes of phytochemical compound in aerial parts of the Lovage plants at different developmental stages as well as antioxidant activity. Methods: The plants were harvested from Hezar Mountain. After drying, essential oils were extracted by steam distillation. To identify the essential components GC and GC-MS was used. Antioxidant activity of samples was examined by diphenylpicrylhydrazyl (DPPH) assay. Results: The average yield of essential oil was respectively, 2.3% and 3.1% and 1.5% respectively, in vegetative, Flowering and seed stage. The oil analysis results showed that 21 compounds were identified in the vegetative stage. β-phellandrene (10.7%) and α-Terpinyl acetate (% 38.9) and Curzerene (% 10.6) were the major compound. in the reproductive stage, 22 compounds were identified including β-phellandrene (20.3%) and α-Terpinyl acetate (% 20.4) and γ-Cadinene (12.1%). in the seed stage β-phellandrene (21.1%) and α-Terpinyl acetate (% 25.3) and Sabinene (10.2%) were the highest. Analysis of variance showed that the effect of harvesting time has significant effect on plant height, stem branch number and yield of oil. The Higher antioxidant power was observed respectively in the flowering stage (83%), vegetative stage (68%) and seed stage (60%). Conclusion: The phytochemical and antioxidant compounds in Levisticum officinale depend on the phenological stage.